COVID-19 History Increases the Anxiety of Mothers with Children in Intensive Care during the Pandemic in Turkey - Eren Yildiz; Zuhal Koc Apaydin; Berna Alay; Zübeyde Dincer; Emrah Cigri (MDPI AG, 2022)
This study aimed to examine the mental status of mothers whose children were hospitalized during the COVID-19 pandemic, especially in places where risk factors are higher such as pediatric intensive care units, and to contribute to the development of psychological health policies, especially for these high-risk groups in epidemic situations. Method: This descriptive cross-sectional study was conducted between January 2021 and July 2021. The population of the study was mothers whose children were hospitalized in the pediatric intensive care unit during the study period. Data collection was carried out via a face-to-face interview method by experienced nurses working in pediatric clinics using a sociodemographic data form, the Beck Anxiety Inventory, the Beck Depression Inventory, the Fear of COVID-19 Inventory, and the Coronavirus Anxiety Inventory. Results: The median age of the participants was 33 (min: 21, max: 50). The Beck Anxiety score was affected by the child’s diagnosis, location, and history of COVID-19 (* P = 0.011, ** P = 0.018, and *** P = 0.002, respectively). Similarly, the Beck Depression score was affected by the child’s diagnosis and history of COVID-19 in a relative (* P = 0.034 and ** P = 0.037, respectively). The Coronavirus Anxiety score was affected by a history of COVID-19 in a relative and work status (* P = 0.040 and ** P = 0.005, respectively), while the Fear of COVID-19 score was not significantly affected by any variable. In a logistic regression model, previous COVID-19 experience was independently associated with anxiety; a history of COVID-19 increased the risk of developing anxiety by approximately 15 times (odds ratio: 14.915, 95% CI: 2.075–107.192). Conclusion: When children of mothers with a history of COVID-19 are hospitalized, special attention should be given to their mothers concerning psychological support and assistance.
Keywords: COVID-19; mothers; anxiety; pediatric intensive care units; mothers; COVID-19; anxiety; pediatric intensive care units; Pediatrics; RJ1-570; Article; 3. Good health